The state-of-art in Health Psychology - Oblitas, Luis A. (2008)
Studies on the scientific background of Health Psychology are discussed, including the conceptual definition, as well as the bio-psycho-social model that characterizes it. The relation between health and behavior is described in order to have a better understanding of health and illness, as well as about the pathogenic and immunology issues related to behavior. The main contributions of Health Psychology to improve life quality and health are described. Moreover, medical psychology, psychosocial coping of illness, as well as intervention strategies, are discussed. Health Psychology becomes a good alternative for the understanding of health and illness mechanisms, as well as for the prevention process and illness treatment related to psychological components.